ANALISIS KESEDIAAN MASYARAKAT UNTUK MEMBAYAR (Willingness to Pay) BIAYA PENGADAAN AIR BERSIH (PDAM) DI KOTA PEKANBARU - Sandhyavitri, Ari; Putri, Nessa Riana; Fauzi, Manyuk; Sitikno, Sigit (Jurnal Teknik Sipil dan Perencanaan, 2016)
This paper investigated how much the public's willingness to pay (WTP) for the cost of public water supply services (PDAM) in Pekanbaru City. This research also projected how much urban water demand of this city for period of 2014-2032. This study divided samples into two categories, namely (i) middle and high income society, and (ii) low income one. These categories were based on the type of house ownership, and the percentage of low income family in this city This research obtained two main factors affected to the WTP for public water services (Y), such as; (i) the number of family members (X1), and (ii) the amount of family income (X2). The equation formula of Y = -677.816 + 12934.502 X1 + 0.012 X2. The average public’s willingness to connect to PDAM for the middle and high income society was 62.13% and for the lower class was 44.44%.There was a trend that the middle and high incomes society’s water demand was relatively higher than that the lower one.  The amount of water tariffs for middle and high income class society was at the average of Rp.6.615 / m3, and Rp.4.971/m3 for the lower income one. This tariff was higher than the average tariff in 2014 (Rp. 3,300 / m3). The water supply capacity in 2014 was estimated to 620 l/sec, and it was projected that water demand in 2032 will increase to 3,946 l/sec (three folds). Tulisan ini meneliti berapa besar keinginan masyarakat untuk membayar biaya pelayanan pengadaan air bersih (PDAM) di Kota Pekanbaru dan membuat proyeksi kebutuhan air bersih Kota Pekanbaru 2014-2032. Sampel calon pelanggan air bersih dalam penelitian ini dibagi atas dua kategori, yaitu (i) masyarakat kelas menengah keatas, dan (ii) kelas menengah kebawah. Penelitian ini mengidentifikasi dua faktor utama yang mepengaruhi keinginan masyarakat menengah ke atas membayar pelayanan air bersih PDAM (Y), yaitu; (i) jumlah anggota keluarga (X1), dan (ii) besarnya pendapatan keluarga (X2), dengan formula Y= -677,816 + 12934,502 X1 + 0,012 X2. Keinginan untuk menyambung pada masyarakat menengah keatas sebesar 62,13% dan di kelas menengah kebawah adalah 44,44%. Besarnya tarif air bersih yang diinginkan masyarakat menengah keatas Rp.6.615/m3 dan Rp.4.971/m3 untuk kelas menengah kebawah.Tarif ini lebih tinggi dari rata-rata tarif PDAM pada tahun 2014 yaitu Rp. 3.300/m3.Kapasitas pasokan PDAM air pada tahun 2014 adalah 620 l/detik, namun diproyeksikan kebutuhan air bersih meningkat menjadi 3.946 ll / detik untuk tahun 2032.